Murder of a needled knitter : a Scumble River mystery - Swanson, Denise (Swanson, Denise. Scumble River mysteries., 2014)
When murder and mayhem join them on their honeymoon cruise, including Skye's mother, who has booked the same trip with her knitting group, newlyweds Skye Denison and Wally Boyd try not to jump ship.